Language Anxiety and Its Effect on Studentsâ Speaking Performance - Sulistyorini, Dwi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This study is about the analysis of language anxiety factors affecting Technical department 51 Batch 4th semester cadetsâ speaking performance. The aim of this study is to list the language anxiety factors that affect cadetsâ speaking performance and to explain how the language anxiety can affect cadetsâ speaking performance. The data of this study were taken from questionnaire, open-ended interview, and studentsâ speaking performance score. There were 60 cadets from two classes on class F and G of Indonesia Merchant Marine of Semarang. The questionnaire data were analyzed based on Horwitzâs theory of Language Anxiety. Then for the language anxiety factors, each statement was calculated to know five chosen statement. The relation between language anxiety and studentsâ speaking performance were analyzed based on studentsâ interview answer, speaking score, and anxiety level. There were five factors of language anxiety affects studentsâ speaking performance: 1) lack of preparation during language class, 2) peer-pressure in language as a whole, 3) sudden-activity in class, 4) peer-pressure in English speaking, and 5) studentsâ negative attitudes toward English language. There were no solid correlation between studentsâ speaking performance and language anxiety, what made their speaking performance differ from one to another was their linguistic competence and how they cope with their anxiety during speaking class.